Investigation of the formation of the [2(iohexol) + Mg]2+ complex and its fragmentation in electrospray ionization tandem mass spectrometry. (28th November 2016) - Guo, Mengzhe; Yin, Dengyang; Han, Jie; Li, Xiao; Zhang, Liyan; Du, Yan; Wang, Haibo; Guo, Cheng; Tang, Daoquan
Abstract : Rationale: Mass spectrometry has been developed as one of the common tools for the analysis of the organometallic systems in the gas phase over decades. The study of the fragmentation of organics‐metal complexes has attracted much attention since the interesting dissociation pathways exhibited by these compounds are usually different from the protonated analogues. Methods: In this work, iohexol complexed with different dications such as Mg 2 +, Cu 2 + and Zn 2 + have been investigated by electrospray ionization (ESI) tandem mass spectrometry. Additionally, deuterium‐labeling experiments and an analogue of iohexol were utilized to confirm the reaction mechanisms. A computational chemistry method was used to identify the coordination conformation between iohexol and metal ions in the gas phase. UV detection was also used to identify the interaction between iohexol and metal ions in the liquid phase. Results: A special gas‐phase open‐loop reaction of iohexol induced by Mg 2 +, leading to the formation of [iohexol + Mg – H – HI ‐ C3 H4 O] +, was observed in the collision‐induced dissociation of [2(iohexol) + Mg] 2+ complexes. Moreover, theoretical calculation shows the proposed coordination configuration of iohexol/Mg 2 + complexes. The Mg 2 + could have tetrahedral coordination with two iohexol molecules. Conclusions: The percent study is a case for better understanding the formation of a typical organic/metal complex and its gas‐phase fragmentation reaction. In addition, it provides useful information for researchers working on analysis or structural elucidation of complicated compounds which contain the iohexol analogues. Copyright © 2016 John Wiley & Sons, Ltd.